Ductal carcinoma in situ of the breast: evaluation of the treatment options - Vidali, Cristina (Radiology and oncology (Ljubljana), 1997)
From January 1978 to December 1994, 87 patients with ductal carcinoma in situ (DCIS) of the breast were observed at the Centro Oncologico of Trieste, 43/98 (49.5%) patients underwent mastectomy; 42/87 (48.2%) quadrantectomy and radiation therapy and 2/87 (2.3%) lumpectomy alone. The local recurrence rate was 3.4% (3/87 cases), with a median follow-up of 69 months. The 3 patients who relapsed had been treated by conservative surgery and radiation therapy; they had a salvage mastectomy and are alive and free of disease. The 15-year actual overall and disease-free survivals are 100% and 89.9% respectively. In our retrospective study the conservative treatment proved to be a good alternative to mastectomy in patients with DCIS.
Keywords: Breast neoplasms; Carcinoma in situ; Carcinoma, intraductal, noninfiltrating; Radiotherapy; Surgery; Treatment outcome